"Keep the Damned Women Out" : The Struggle for Coeducation - Malkiel, Nancy Weiss (Book collections on Project MUSE., 2016)
"As the tumultuous decade of the 1960s ended, a number of very traditional, very conservative, highly prestigious colleges and universities in the United States and the United Kingdom decided to go coed, seemingly all at once, in a remarkably brief span of time. Coeducation met with fierce resistance. As one alumnus put it in a letter to his alma mater, "Keep the damned women out." Focusing on the complexities of institutional decision making, this book tells the story of this momentous era in higher education--revealing how coeducation was achieved not by organized efforts of women activists, but through strategic decisions made by powerful men. In America, Ivy League schools like Harvard, Yale, Princeton, and Dartmouth began to admit women; in Britain, several of the men's colleges at Cambridge and Oxford did the same. What prompted such fundamental change? How was coeducation accomplished in the face of such strong opposition? How well was it implemented? Nancy Weiss Malkiel explains that elite institutions embarked on coeducation not as a moral imperative but as a self-interest means of maintaining a first-rate applicant pool. She explores the challenges of planning for the academic and non-academic lives of newly admitted women, and shows how, with the exception of Mary Ingraham Bunting at Radcliffe, every decision maker leading the charge for coeducation was male. Drawing on unprecedented archival research, [this book] is a breathtaking work of scholarship that is certain to be the definitive book on the subject."--Jacket.